ETHICAL ISSUES IN THE USE OF AI IN MEDICINE - Atamuratova Feruza Sadullaevna; Zainiddinova Zamira; Shomuradova Kamila (Web of Journals Publishing, 2025)
In the 21st century of scientific and technological progress, one of the many manifestations of the development of modern technologies has become artificial intelligence or artificial cognitive system [1]. Today, AI algorithms are used to diagnose diseases, predict treatment outcomes, manage medical data and even develop drugs. But along with this, a number of ethical issues arise: responsibility for errors, ensuring transparency and controllability of AI work, privacy issues [2]. In addition, the use of artificial intelligence has great potential for the medicine of the future [3]. Artificial intelligence has great potential to transform and systematize the entire health care system as a whole. At the moment, there are a number of examples of the results of the implementation of various types of technologies in medicine, such as the IBM program Watson in oncology, Celsus system, Sky app Vision. Based on statistics from the journal Nature, it is clear that between 2015 and 2020, the number of published studies related to the application of technology in the field of medicine has increased rapidly. There are many more such examples, but only one conclusion can be drawn from them - AI in the field of healthcare is undoubtedly one of the main assistants of the current generation of doctors. On the one hand, the introduction of highly specialized neural networks and artificial intelligence in medicine allows not only to significantly improve the quality of services provided in the field of diagnostics, treatment and prevention, but also to optimize the processes of information processing in multitasking conditions. On the other hand, a number of problems arise that require detailed study, which creates a solid basis for studying previously poorly studied aspects. When considering any topic in medicine, all the threads lead us to the root of this topic - ethical problems. Consequently, the topic of introducing artificial intelligence has become no exception, due to its versatility and relevance, each time it gives rise to more and more questions, mainly ethical ones.
Keywords: artificial intelligence, ethics, medicine, responsibility, personal data.